2020
DOI: 10.31234/osf.io/7bexk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Test of a Deviance Regulation Theory Intervention Among First Year College Student Drinkers: Differential Effects via Frequency and Quantity Norms

Abstract: OBJECTIVE: First-time-in-college (FTIC) students, or college freshmen, are at a heightened risk of experiencing alcohol-related consequences, as these individuals are relatively inexperienced with alcohol and have tremendous pressure to assimilate to new norms. The current study investigates the use of a Deviance Regulation Theory (DRT) intervention, presented in a web-based format, to increase the use of Protective Behavioral Strategies (PBS) among FTIC students. METHOD: FTIC students (n = 157) completed week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, more recent interventions that sought to increase PBS by leveraging personal and social identity have shown more promise (see Dvorak, et al, 2015Dvorak, et al, , 2018. Leary et al (2020) suggested that this may be the result of changes in personal identity around safe drinking. However, to date, this has not been evaluated as there is no validated measure of safe drinking identity.…”
Section: Protective Behavioral Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent interventions that sought to increase PBS by leveraging personal and social identity have shown more promise (see Dvorak, et al, 2015Dvorak, et al, , 2018. Leary et al (2020) suggested that this may be the result of changes in personal identity around safe drinking. However, to date, this has not been evaluated as there is no validated measure of safe drinking identity.…”
Section: Protective Behavioral Strategiesmentioning
confidence: 99%
“…In contrast, recent interventions that leverage theories of identity may be better suited to lasting and enduring change. For example, deviance regulation theory (DRT) is grounded in social and personal identity theory (Blanton & Christie, 2003) and interventions incorporating DRT have shown efficacious long-term outcomes (Dvorak et al, 2015(Dvorak et al, , 2017Leary et al, 2020), perhaps due to identity change. Similarly, Caldwell et al (2018) suggested assessing changes in identity, rather than changes in behavior, will ultimately predict long-term outcome within interventions.…”
Section: Limitations Ethical Considerations and Diversity Issuesmentioning
confidence: 99%